Механизм газожидкостного взаимодействия в системе аммиак – диоксид углерода – вода - Цейтлин, Моисей Абрамович; Райко, Валентина Федоровна (Київський політехнічний інститут ім. Ігоря Сікорського, 2021)
З позиції плівкової теорії масопередачі проведено аналіз механізму газорідинної взаємодії в системі NH₃–CO₂–H₂O. Отримано систему кінетичних рівнянь, що повністю описують транспорт компонентів газу в рідину. Експериментальне дослідження абсорбції в зазначеній системі дозволило отримати підтвердження адекватності знайденого математичного опису процесу і отримати кореляції для кінетичних коефіцієнтів абсорбції.

From the standpoint of the film theory of mass transfer, the analysis of the mechanism of gas-liquid interaction in the NH₃–CO₂–H₂O system was carried out. A system of kinetic equations is obtained that completely describe the transport of gas components into liquid. An experimental study of absorption in this system made it possible to confirm the adequacy of the found mathematical description of the process and to obtain correlations for the absorption kinetic coefficients.
Mechanism of gas-liquid interaction in the ammonia – carbon dioxide – water system
Keywords: масопередача; плівкова теорія; абсорбція; аміак; діоксид вуглецю; кінетика абсорбції; математичне моделювання; mass transfer; film theory; absorption; ammonia; carbon dioxide; absorption kinetics; mathematical modeling